Spiritual Dimension in Mental Rehabilitation of Adolescent Drug Addicts: (Case Study at Inabah VII Putra Suryalaya Tasikmalaya) - Rusmana, Asep (Ann Publisher, 2025)
Background. In various regions in Indonesia, drug addiction has experienced an increase, especially in adolescents. Teenagers seem to be good subjects for drug dealers to become users and couriers. Adolescents who are addicted to drugs experience dysfunction in thinking, feeling, speaking, and sensing. Aims. Rehabilitation efforts are needed to help drug-addicted teenagers recover from abnormal conditions. One of the rehabilitation centers for drug addicts is in the Suryalaya Tasikmalaya Islamic boarding school in Inabah VII Putra. Methods. The research method employs a descriptive approach with a qualitative data analysis, utilizing interviews, observations, and primary research data, including files related to the research case. Secondary data sources, such as books, scientific journals, and processed data, are also used for confirmation and triangulation. These data are presented in the form of critical analysis description paragraphs that refer to the creation of a new finding. Result. As for the result of this study, the mental rehabilitation of drug addicts in Inabah uses a spiritual approach in the form of the Suluk TQN method (Bathing, Bathing Repetance, Talqin Dzikir, Prayer). Research was conducted using a descriptive method in a qualitative approach to assess changes in fostered children, both psychologically and spiritually. Conclusion. With a spiritual approach, drug addicts can recover in a better direction and get closer to God. The things that foster children get are free from drugs, changing minds, and a change in mental condition in the form of calm and confidence, being able to change lifestyle, and being able to help and guide people who are affected by drugs.